Kriteria Prioritas Pemilihan Teknologi Pengolahan Limbah Cair Industri Tempe - Cahyaning Kilang Permatasari (Institut Teknologi Sains Bandung, 2021)
The location of tempe processing adjacent to the settlement causes problems. The resulting liquid waste makes people uncomfortable. This is presumably because the liquid waste has not been managed properly, because it is only dumped into the drainage channel. The majority of tempe industrial entrepreneurs are home industries who are not aware of creating a healthy environment by paying attention to liquid waste processing. There are many studies on technology for the tempe industrial wastewater problem, but each technology has advantages and disadvantages. It is necessary to have a system to choose the technology that suits the waste conditions. This research takes a case study in Karanganyar Regency. The Analytical Hierarchy Process (AHP) method is a method of determining priority scale that can accommodate all aspects. Furthermore, a sequence of criteria can be arranged as needed. The results of the analysis with AHP are: technology criteria 31.09%; environment 28.65%; economic 21.74% and social 18.53%. Environmental sub-criteria showed the results of the removal of ammonia 40.56%; treated water quality 30.74%; the amount of mud is 18.91% and the emission level is 9.80%. Technology sub-criteria are ease of operation 28.67%; land area requirement 28.56%; service life of 28.05% and the potential of technology in the midification of 14.72%. Economic sub-criteria with the results of operating costs 34.21%; installation cost 33.28%; maintenance costs 23.78% and HR costs 8.73%. Social sub-criteria with the results of the need for employment of 49.10%; readiness of human resources 19.33%; implementation of construction 16.74% and aesthetics 14.82%. The results of the AHP can be used as input for tempe entrepreneurs, the government and the community to improve the environmental quality of the tempe industrial wastewater. It is hoped that entrepreneurs will find it easier to determine the appropriate technology to treat the tempe industrial liquid waste.